2013
DOI: 10.2298/jsc130130029d
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of thermophysical and transport properties of ternary organic non-electrolyte systems including water by polynomials

Abstract: The description and prediction of the thermophysical and transport properties of ternary organic non-electrolyte systems including water by the polynomial equations are reviewed. Empirical equations of Radojković et al. (also known as Redlich-Kister), Kohler, Jacob-Fitzner, Colinet, Tsao-Smith, Toop, Scatchard et al. and Rastogi et al. are compared with experimental data of available papers appeared in well know international journals (Fluid Phase Equilibria, Journal of Chemical and Engineering Data, Jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…The relationship between the chemical composition of plants and saline condition is of great importance to understand plant adaptation under high salinity. Low leaf K, Ca, and Mg concentrations along with the accumulation of Na were documented in plants growing in high salinity, and have been recorded for some eu-halophytes including many Chenopodiaceae (Albert and Kinzel, 1973;Albert and Popp, 1977;Gulzar et al, 2003;Kachout et al, 2011;Khan et al, 2000a, b;Kudo et al, 2010;Milić et al, 2013;Wiebe and Walter, 1972;Zoerb et al, 2013). Several studies have shown that the accumulation of certain elements in the leaves of some species of eu-halophytes is genetically controlled with poor dependency on the condition of their rhizospheres (Albert, 1982;Breckle, 1986;Krüger and Peinemann, 1996;Matinzadeh et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The relationship between the chemical composition of plants and saline condition is of great importance to understand plant adaptation under high salinity. Low leaf K, Ca, and Mg concentrations along with the accumulation of Na were documented in plants growing in high salinity, and have been recorded for some eu-halophytes including many Chenopodiaceae (Albert and Kinzel, 1973;Albert and Popp, 1977;Gulzar et al, 2003;Kachout et al, 2011;Khan et al, 2000a, b;Kudo et al, 2010;Milić et al, 2013;Wiebe and Walter, 1972;Zoerb et al, 2013). Several studies have shown that the accumulation of certain elements in the leaves of some species of eu-halophytes is genetically controlled with poor dependency on the condition of their rhizospheres (Albert, 1982;Breckle, 1986;Krüger and Peinemann, 1996;Matinzadeh et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Halophytes show different tolerance mechanisms and regulatory pathways and they can be classified into different functional groups accordingly (Milić et al, 2013;Mori et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] In addition, a review 17 was particularly devoted to molecular interactions of binary liquid mixtures containing alcohols, i.e., n-alcohols, branched alcohols and alkanediols in mixtures with aromatics, nitroaromatics, halo-aromatics, amines, n-alkanes, ketones and esters. [11][12][13][14][15][16][17][18][19][20][21][22][23] In addition, a review 17 was particularly devoted to molecular interactions of binary liquid mixtures containing alcohols, i.e., n-alcohols, branched alcohols and alkanediols in mixtures with aromatics, nitroaromatics, halo-aromatics, amines, n-alkanes, ketones and esters.…”
Section: Introductionmentioning
confidence: 99%